Home town - Kidder, Tracy (Random House, Inc., 1999)
" ... Kidder reveals the sheer abundance of life contained within a town's narrow boundaries. Does the kind of small town that many Americans came from, and long for, still exist? Kidder says yes, although not quite in the form we may imagine. A book about civilization in microcosm ..."--Jacket.